Transformational Leadership and Organizational Innovation: The Mediating Role of Organizational Learning - Juliasa, Made; Aristana, I Nengah; Adiandari, Ade Maharini; Widanti, Ni Putu Kusuma (Universitas Mercu Buana, 2025)
Nowadays, innovation has become an important thing for organizations to do. The cause of this situation is the rapid development of business in the era of globalization, where business actors must always be dynamic in seeking and filling opportunities created in the market. This study analyzes the influence of transformational leadership, organizational learning, and organizational innovation. Qualitative and quantitative data were obtained from both primary and secondary sources by conducting interviews, observations, and distributing questionnaires. The population of this study was all export-oriented small and medium enterprises (SMEs) registered with the Department of Trade and Industry in Bali. The sampling technique used saturated sampling with the random sampling method, saturated sampling so that the number of samples obtained was 66 SMEs. The results of this study indicate that leadership has a significant effect on organizational learning and organizational innovation. Organizational learning has been proven to play a role as a mediator in the relationship between transformational leadership and organizational innovation.